Financialization and the rise in co-movement of commodity prices. Issue 5 (2nd September 2016) - Pradhananga, Manisha
Abstract: Between January 2000 and June 2008, the FAO food price index rose by 96%. Besides the magnitude, the price rise was remarkable for the broad range of commodities affected; prices of agriculture commodities, energy, and metals all rose and fell together. These dramatic developments coincided with a massive inflow of investment in the commodities futures market, and the rise of commodities as an investment class. In this paper, I study causal links between the increase in the co-movement between commodity prices and financialization of the commodities futures market. I extract common factors from a group of 40 commodities using the PANIC method and include it in a factor-augment VEC model along with a proxy of financialization. Results show that financialization of the commodities futures markets can explain the recent rise in co-movement between commodity prices, after accounting for macroeconomic variables.